Observational Analysis of Kiai's Guidance Strategy in Teaching Qira'at Imam Nafi' Through Warsh Narrative in Al-Bidayah Cipongkor Qur'anic Boarding School - Fathurrohman, Asep Ahmad; Dewi, Ratna (Jurnal Keislaman, 2025)
This paper departs from the observation of the guidance strategy used by Kiai in teaching Qira'atImam Nafi' through Riwayat Warsh in an Islamic educational institution, namely the Al-Bidayah Cipongkor Al-Qur'an Islamic Boarding School. This paper uses a qualitative approach with the type of literature study from various literature sources and field studies in the form of results from observations during the service. The analysis technique of this paper is in the form of observations during the service which are used to analyze the teaching-learning process between Kiai and santri in the learning process. This paper produces findings that the most effective guidance strategy in teaching Qira'at Sab'ah is the Jibril method, which focuses on memorization, accompanied by the application of intensive recitation exercises to improve the skill of reading the Qur'an according to Riwayat Warsh. In addition, the role of kiai in providing spiritual motivation is a key factor in maintaining the consistency of santri in learning this Qira'at. This paper concludes and contributes to the understanding of the importance of kiai guidance methods in preserving the Qira'at tradition as part of the Islamic scientific heritage.